A longitudinal study of reciprocal risk between mental and substance use disorders among Mexican youth. (October 2018) - Borges, Guilherme; Benjet, Corina; Orozco, Ricardo; Medina-Mora, Maria Elena
Abstract: Objective: Cross-sectional studies have documented a large co-occurrence of alcohol, drug and tobacco use and disorders with mood, anxiety and disruptive behavior disorders. Longitudinal research among adolescents is much more limited and inconsistent. We tested for possible prospective associations of alcohol, drug, and tobacco use and disorders with an array of anxiety, mood and disruptive behavior disorders from adolescence to early adulthood. Methods: We estimated prospective associations from a follow-up conducted in 2013 (n = 1071; ages 19–26) of the original Mexican Adolescent Mental Health Survey conducted in 2005 (ages 12–17), by using Relative Risk (RR) estimates. Results: Prior drug and tobacco use and disorders had small to modest associations with subsequent mood and disruptive behavior disorders (significant RR ranging from 1.42 to 3.30). Inversely, prior mood (RR = 1.54), anxiety (RR = 1.20) and disruptive behavior disorders (RR = 1.61) increased risk of any subsequent substance use disorder. Prior anxiety disorders increased the risk of drug use disorder (RR = 1.69) and prior disruptive behavior disorders increased risk of incident alcohol (RR = 1.70) and drug use (RR = 2.61) disorders. Attention deficit/hyperactivity disorder, in particular, was related to incident alcohol (RR = 2.08), drug (RR = 3.66), nicotine dependence (RR = 2.57) and any substance use disorders (RR = 2.18). Discussion: We found limited longitudinal evidence of bidirectional influences between substance use disorders and mood, anxiety and disruptive behavior disorders with effect sizes that were modest at most under all circumstances. Mechanisms for these complex relationships need to be addressed in future research. Highlights: Few longitudinal relationships between incidence of substance use and mental disorders. Most associations were from prior mental disorders to subsequent substance use disorders. Effect sizes (RR) were small to modest for most associations. ADHD was related to an incident alcohol, drug and tobacco use disorder.